HUBUNGAN ANTARA KONSEP DIRI DENGAN FUNGSI PSIKOLOGIS MAKE-UPPADA MASA EMERGING ADULTHOOD - Clara Stascia (CALYPTRA, 2018)
The period of adulthood emerging development starts from the age of 18-25 years. At this time individuals begin to be characterized by changes in development such as the development of reproductive systems, broader vision, and more can recognize the identity that is in him. Make-up or cosmetics have a psychological function that is make-up seduction function and camouflage make-up function. This study aims to determine the relationship between self-concept with the psychological function of make-up in the emerging adulthood. The method used in this study is quantitative explanative survey by spreading the questionnaire on the subject of 147 respondents. The sample of this research was done non-randomly with accidental quota sampling technique. Criteria subjects aged 18-25 years who use make-up 2 times in everyday life and minimal use 3 types of makeup that is, face powder, lipstick, BB cream. The hypothesis in this study was tested by Spearman Corellation technique. The results of this study showed no relationship between self-concept with the psychological function of make-up (r = 0,017; p = 0,417). In terms of the psychological function of make-up, there were 39 subjects (26.5%) classified as seduction, 84 subjects (57.1%) were classified as camouflage-seduction, 24 subjects (16.3%) were classified as camouflage. The subject of this study did not use the make-up function as the basis for the use of make-up. This is because the subject is accepted in the social environment in a positive way, making the subjectremains positive and confident even when not using make-up.